Hemipogon trilobatus sp. nov. (Apocynaceae: Asclepiadoideae), a new microendemic from Chapada dos Veadeiros, Central Brazil - Bitencourt, Cássia; Santos, Amanda P.B.; Snak, Cristiane; Rapini, Alessandro (European Journal of Taxonomy, 2020)
Hemipogon s. str. (Apocynaceae: Asclepiadoideae) currently consists of three species sharing an erect herbaceous habit, narrow leaves and corona-less flowers with urceolate, internally bearded corolla, that are mainly distributed in savannahs of the Cerrado biodiversity hotspot, South America. Here, we describe and illustrate a new species of Hemipogon, H. trilobatus Bitencourt & Rapini sp. nov., from an open savannah in Chapada dos Veadeiros, Central Brazil. Hemipogon trilobatus sp. nov. differs from the other species of the genus mainly by the presence of a reduced staminal corona with 3-lobed lobes, but also by opposite leaves and triangular anthers. Distribution and habitat data, as well as a key and a comparative table to distinguish the four species currently accepted in Hemipogon s. str., are provided. Based on criteria B2ab(i,ii,iii,iv) of the International Union for Conservation of Nature (IUCN), the species is provisionally assessed as Critically Endangered.